A COMPARISON BETWEEN OPEN AND CLOSED HEMORRHOIDECTOMY - Rehman, Khalil -ur-; Hasan, Azmat; Taimur, Muhammad; Imran, Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Haemorrhoidectomy is associated with complications including pain, bleeding and wound infection which can result prolonged hospital stay. Haemorrhoidectomy is considered to provide a better outcome in terms of postoperative pain and wound healing. Aims were to compare postoperative pain, bleeding, operating time and wound healing in patients undergoing open and closed haemorrhoidectomy. Methods: This comparative study was conducted in the surgical department at Fauji Foundation Hospital, Rawalpindi from December 13, 2006 to December 31, 2011. Consecutive patients, both male and female, presenting with 3rd and 4th degree haemorrhoids in the surgical Outpatient Department were included in this study. Half of the patients were assigned to the open haemorrhoidectomy group while the other half was put in the closed haemorrhoidectomy group. Each patient was evaluated by detailed history and examination. Both digital rectal examination (DRE) and proctoscopy were done to confirm the diagnosis. Results: A total of 260 patients were assessed, 130 in each group. In the open group, 52 patients experienced mild pain and 78 moderate while in the closed group, 30 patients experienced mild pain, 87 moderate and 13 patients severe pain. All 130 patients in the closed group showed complete wound healing after 2 weeks as compared to only 66 patients in the open group with a p<0.001. Early and late postoperative bleeding was similar in both groups. Conclusions: The closed technique provides a better outcome in terms of less postoperative bleeding and complete wound healing, but it is associated with more pain. Keywords: Open haemorrhoidectomy, closed haemorrhoidectomy, postoperative, pain